Cisplatin binding to human serum albumin: a structural study1. Issue 46 (11th June 2015) - Ferraro, Giarita; Massai, Lara; Messori, Luigi; Merlino, Antonello
<x xml:space="preserve">Abstract</x> The reaction between cisplatin and human serum albumin (HSA) was investigated by X-ray crystallography and crystal structures of the cisplatin/HSA adduct were eventually solved for the first time.